To study the correlation of symptoms of angina with the diagnosis of ST Segment Elevation Myocardial Infarction (STEMI) - V.R. Mujeeb; Prashant Jambunathan; Arun Tyagi (International Journal of Medical Research and Review, 2017)
Introduction: Chest pain is amongst the commonest causes of visits to the emergency department. A rapid assessment with a prompt evaluation with an electrocardiogram clinches the diagnosis in most cases. However, with ever increasing strain on our limited resources, patient reported symptoms are central to initial assessment and must decide the course of action. Although considered ominous signs requiring further, often emergent, assessment, data on correlation of symptoms of angina with ST segment elevation is limited in contemporary literature.Methodology: 230 patients with biomarker proven ST segment elevation myocardial infarction (STEMI) were studied and assessed for frequency of the four, patient reported, cardinal symptoms of angina, namely retrosternal chest discomfort, diaphoresis, palpitations and radiation. We assessed the relative presence or absence of these supposedly cardinal symptoms of angina and set out to classify the most important symptoms of angina.Results: Our study shows that presence of three or more above symptoms is associated with a much higher possibility of an actual STEMI as opposed to only one symptom. Furthermore, a measurable increase in the probability of MI exists, when the number of patient reported symptoms increases from none to all four, as mentioned above. Though the study also reaffirmed the association between hypertension and Type 2 Diabetes Mellitus with acute coronary syndromes, our study was neither powered, nor designed to study this association.Conclusions: Patient reported symptoms have a direct and additive correlation with STEMI. A quick but detailed history in the emergency department is of paramount importance to identify high risk patients.